Antibacterial Use Is Associated with an Increased Risk of Hematologic and Gastrointestinal Adverse Events in Patients Treated with Gemcitabine for Stage IV Pancreatic Cancer. (17th March 2020) - Corty, Robert W.; Langworthy, Benjamin W.; Fine, Jason P.; Buse, John B.; Sanoff, Hanna K.; Lund, Jennifer L.
Abstract: Background: Preclinical evidence has demonstrated that common intratumor bacteria metabolize the chemotherapeutic drug gemcitabine. The significance of this bacterial metabolism pathway, relative to the known metabolic pathways by host enzymes, is not known. We hypothesized that bacterial metabolism is clinically significant and that "knockdown" by antibacterial therapy has the unintended effect of increasing the effective dose of gemcitabine, thereby increasing the risk for gemcitabine‐associated toxicities. Materials and Methods: We reanalyzed the comparator arm of the MPACT trial (NCT01442974), made available through Project Data Sphere, LLC (CEO Roundtable on Cancer's Life Sciences Consortium, Cary, NC; www.projectdatasphere.org ). In this arm, 430 patients with metastatic pancreatic adenocarcinoma were treated with gemcitabine. We used the Anderson‐Gill survival model to compare the risk of developing an adverse event after antibacterial prescription with time unexposed to antibacterials. Adverse events of grade 3 and greater were considered at three levels of granularity: all aggregated into one endpoint, aggregated by class, and taken individually. Antibiotic exposures were analyzed in aggregate as well as by class. Results: Antibacterial exposure was associated with an increased risk of adverse events (hazard ratio [HR]: 1.77; confidence interval [CI]: 1.46–2.14), any hematologic adverse event (HR: 1.64; CI: 1.26–2.13), and any gastrointestinal adverse event (HR: 2.14; CI: 1.12–4.10) but not a constitutional (HR: 1.33; CI: 0.611–2.90) or hepatologic adverse event (HR: 0.99; CI: 0.363–2.71). Among specific adverse events, antibacterial exposure was associated with an increased risk of anemia (HR: 3.16; CI: 1.59–6.27), thrombocytopenia (HR: 2.52; CI: 1.31–4.85), leukopenia (HR: 3.91; CI: 1.46–10.5), and neutropenia (HR: 1.53; CI: 1.07–2.17) but not any other specific adverse events. Conclusion: Antibacterial exposure was associated with an increased risk of gemcitabine‐associated, dose‐limiting adverse events, including aggregate hematologic and gastrointestinal events, as well as four specific hematologic adverse events, suggesting that intratumor bacteria may be responsible for a clinically significant portion of gemcitabine metabolism. Alternative avenues of evidence will be necessary to confirm this preliminary finding and assess its generalizability. There is plentiful opportunity for similar analyses on other clinical trial data sets, where gemcitabine or other biomimetic small molecules were used. Implications for Practice: Patients treated with gemcitabine for metastatic pancreatic ductal adenocarcinoma have an increased rate of gemcitabine‐associated toxicity during and after antibiotic therapy. This observation is consistent with preclinical evidence that intratumor bacteria metabolize gemcitabine to an inactive form. Further research is needed to determine whether this observation merits any changes in clinical practice. Abstract : Previous reports have suggested a potential interaction between gemcitabine and the host microbiome. By reanalyzing an arm of a clinical trial in which patients were treated with gemcitabine, this article provides observational clinical evidence consistent with this potential interaction.